Associations between apathy and comprehensive frailty as assessed by the Kihon Checklist among community‐dwelling Japanese older adults. Issue 5 (26th June 2022) - Maruta, Michio; Shimokihara, Suguru; Makizako, Hyuma; Ikeda, Yuriko; Han, Gwanghee; Akasaki, Yoshihiko; Hidaka, Yuma; Kamasaki, Taishiro; Kubozono, Takuro; Ohishi, Mitsuru; Tabira, Takayuki
Abstract : Background: Frailty is a multidimensional condition characterised by reduced physical and psychological resilience. Older adults also frequently demonstrate apathy, suggesting that it shares similar neuro‐physiological pathways with frailty. This cross‐sectional study aimed to investigate the association between apathy and frailty as defined by a comprehensive assessment. Methods: We analyzed 882 older adults (mean age: 74.4 ± 6.4 years; 62.1% female) who participated in a community‐based health check survey (Tarumizu Study). Apathy was measured by the Geriatric Depression Scale‐3A, a three‐item subset of the Geriatric Depression Scale‐15, and frailty by the Kihon Checklist of physical, psychological, functional, and social status. Associations were examined by multinomial logistic regression with frailty status (robust, pre‐frailty, frailty) as the dependent variable, apathy as the independent variable, and sociodemographic factors, medications, cognitive function, functional capacity, and mood symptoms as potential confounders. Results: Apathy was observed in 23.7% of individuals, and logistic regression revealed significant associations with both pre‐frailty and frailty after confounder adjustment (pre‐frailty: odds ratio (OR) 1.80, 95% CI 1.22–2.64; frailty: OR 3.24, 95% CI 1.63–6.42). Participants with apathy also exhibited greater deficits in the Kihon Checklist subdomains instrumental activities of daily living ( P  = 0.022), physical function ( P  < 0.001), oral function ( P  < 0.001), and cognitive function ( P  = 0.001). Conclusions: Our findings underscore the importance of comprehensive frailty assessment and demonstrate that apathy can have pervasive deleterious effects on geriatric health.